Meminimalisir Stres Kerja Dan Turnover Intention (Studi Kasus Pegawai Perbankan Kota Jambi) - Ubaidillah Ubaidillah (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2021)
This study aims to examine the factors that influence turnover intention, namely work stress and work environment, the sample in this study is banking employees in the city of Jambi. The data collection method is using a questionnaire and analyzed using verification analysis, the analytical tool in this study is using Partial Least Square (PLS). The results of this study will explain whether or not there is an influence of the factors studied on the high or low turnover intention experienced by individuals in working at the Jambi City Banking.